Lack of repeatability of radiomic features derived from PET scans: Results from a 18F‐DCFPyL test–retest cohort. Issue 6 (11th January 2023) - Werner, Rudolf A.; Habacha, Bilêl; Lütje, Susanne; Bundschuh, Lena; Kosmala, Alekandser; Essler, Markus; Derlin, Thorsten; Higuchi, Takahiro; Lapa, Constantin; Buck, Andreas K.; Pienta, Kenneth J.; Lodge, Martin A.; et al.
Abstract: Objectives: PET‐based radiomic metrics are increasingly utilized as predictive image biomarkers. However, the repeatability of radiomic features on PET has not been assessed in a test–retest setting. The prostate‐specific membrane antigen‐targeted compound 18 F‐DCFPyL is a high‐affinity, high‐contrast PET agent that we utilized in a test‐retest cohort of men with metastatic prostate cancer (PC). Methods: Data of 21 patients enrolled in a prospective clinical trial with histologically proven PC underwent two 18 F‐DCFPyL PET scans within 7 days, using identical acquisition and reconstruction parameters. Sites of disease were segmented and a set of 29 different radiomic parameters were assessed on both scans. We determined repeatability of quantification by using Pearson's correlations, within‐subject coefficient of variation (wCOV), and Bland–Altman analysis. Results: In total, 230 lesions (177 bone, 38 lymph nodes, 15 others) were assessed on both scans. For all investigated radiomic features, a broad range of inter‐scan correlation was found ( r, 0.07–0.95), with acceptable reproducibility for entropy and homogeneity (wCOV, 16.0% and 12.7%, respectively). On Bland–Altman analysis, no systematic increase or decrease between the scans was observed for either parameter (±1.96 SD: 1.07/−1.30, 0.23/−0.18, respectively). The remaining 27 tested radiomic metrics, however, achieved unacceptable high wCOV (≥21.7%). Conclusion: Many common radiomic features derived from a test–retest PET study had poor repeatability. Only Entropy and homogeneity achieved good repeatability, supporting the notion that those image biomarkers may be incorporated in future clinical trials. Those radiomic features based on high frequency aspects of images appear to lack the repeatability on PET to justify further study.